Friendship, attitudes, and behavioral intentions of cisgender heterosexuals toward transgender individuals. Issue 2 (3rd April 2017) - Barbir, Lara A.; Vandevender, Anna W.; Cohn, Tracy J.
ABSTRACT: Lesbian, gay, and bisexual (LGB) individuals have begun to gain an acceptance that transgender people have yet to achieve. Previous literature has found the significant effect of Allport's contact hypothesis on reducing negative attitudes toward LGB individuals. Attention has recently turned to the implications of social contact for reduction of transphobic attitudes, with one study demonstrating efficacy. The present study examined the relationships between cisgender heterosexual college students' social contact with transgender individuals, operationalized as number of friendships, and self-reported attitudes and behavioral intentions toward transgender individuals. A sample of 342 undergraduate students at a mid-sized public university completed questions about attitudes and behaviors toward transgender individuals and their transgender friendship experiences. In multivariate analysis of variance, significant differences between participants who reported having zero versus at least one transgender friend across negative intentions, negative attitudes, positive intentions and views, and supportive public intentions toward transgender individuals were found, supporting the contact hypothesis. These findings suggest that having friendships with transgender individuals is associated with reduced prejudice and discrimination and, moreover, greater acceptance and support of transgender people. Implications for increasing acceptance of transgender individuals are discussed.